Self-assembly of a unique 3d/4f heterometallic square prismatic box-like coordination cage. Issue 23 (26th May 2016) - Li, Li; Zhang, Yingjie; Avdeev, Maxim; Lindoy, Leonard F.; Harman, David G.; Zheng, Rongkun; Cheng, Zhenxiang; Aldrich-Wright, Janice R.; Li, Feng
Abstract : A unique, slightly distorted square prismatic, box-like coordination cage of type [Cu6 Dy8 L8 (MeOH)8 (H2 O)6 ](NO3 )12 · χ solvent has been synthesized via the supramolecular assembly between a non-centrosymmetric Dy(iii ) metalloligand and Cu(ii ) nitrate. Abstract : We present the synthesis and characterization of a unique, slightly distorted square prismatic, box-like coordination cage of type [Cu6 Dy8 L8 (MeOH)8 (H2 O)6 ](NO3 )12 · χ solvent obtained via the supramolecular assembly between a non-centrosymmetric Dy(iii ) metalloligand and Cu(ii ) nitrate. Magnetic susceptibility measurements indicate that the complex behaves as a single-molecule magnet.